PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS STEM UNTUK MENINGKATKAN KEMAMPUAN KREATIVITAS MATEMATIKA - Dwi Risky Arifanti; Sitti Zuhaerah Thalhah; Mafidapuspadina Mafidapuspadina; Muhammad Muzaini (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Nowadays, in order to produce minimum graduates with graduate competency standards abilities and have ability to think creatively at work, it is necessary to develop comprehensive, integrated and systematic learning competencies such as development of STEM-based LKPD teaching materials as learning system that leads student’s mindsets in solving problem, think logically, creatively, independently, mastering technology, and being able to apply it in works. This research aims to find out how the process and quality of LKPD development as STEM-based teaching materials to improve student’s creativity abilities. The type of research used is R&D which consists of Define, Design, Development, and Disseminate. The research subjects consisted of three expert validators and students. The object of research is STEM-based LKPD to improve student’s creativity abilities. Data collection techniques used in the form of product feasibility data, response data and student creativity ability data. The instruments used are LKPD validation questionnaires, student response questionnaires, and questionnaires for student’s creativity abilities. Data analysis techniques are feasibility data analysis, response data analysis, and description of creativity abilities. The results showed that the LKPD developed is a valid criterion and can be used with minor revisions based on the assessment conducted by the validator covering aspects of content, language, and presentation quality. The quality of LKPD development with the validation of several experts, including language and completion of instructions in mathematical creativity ability skills, demonstrates that all problems can be used and declared usable. As well as the ability of mathematical creativity is 10% at the level of very creative, 30% at the creative level, 45% at the level of quite creative, 12% at the level of less creative, and 0% at the level of uncreative.